Aktywne procesy w systemie derywacji przyimków - Tsoi, Aleksander (Studia Rossica Posnaniensia, 2017)
The Russian language is constantly supplemented with derivative prepositions. Supplementing the language system with new lexical units is a continuous process. The main ways of forming derivative prepositions are transposition and diffusion.